The use of Dermacell® in Fingertip Injury - Wu, Tsung-Hsuan; Giampietro Bertasi (Journal of Clinical Case Reports and Images, 2019)
Matrices or tissue scaffolds provide a collagen structure for tissue remodelling while the removal of viable cells aims to minimize or prevent inflammatory or immunogenic response. Allograft collagen scaffold can support the patient’s own cellular ingrowth, ingeneered to minimize an immune response and to yeld a bio-compatible matrix and support incoming cellular growth. The decellyularized dermis retains its growth factors, native collagen scaffold, and elastin, thanks to a LifeNet Health proprietaryprocessin technology.
Keywords: Finger tip injury